The impact of host language proficiency across the immigrants' earning distribution in Spain - Santiago Budría; Carlos Martinez de Ibarreta; Pablo Swedberg (IZA Journal of Development and Migration, 2017)
This paper explores the impact of Spanish language proficiency on immigrant earnings in Spain using an instrumental variable quantile regression approach. The impact is on average roughly 17.2% but varies substantially across the earning distribution. The return to destination language proficiency actually ranges from zero at the bottom quantiles to 30% at the top quantile of the earning distribution. These findings suggest that the benefits derived from host language knowledge are particularly important among individuals with stronger unobserved abilities and marketable skills and that language training policies targeted at specific immigrant population categories may be ineffective from a labor market earning perspective.
Keywords: F22; J24; J61; 330; Immigration; Spanish language proficiency; Earnings; Instrumental variable quantile regression (IVQR)